2020
DOI: 10.26418/jc.v6i1.43345
|View full text |Cite
|
Sign up to set email alerts
|

Kejadian interaksi obat pada pasien HIV/AIDS yang menerima antiretroviral di RSUD Dr. Soedarso Pontianak periode 2018

Abstract: Latar belakang: Infeksi virus HIV mengakibatkan terjadinya penurunan sistem kekebalan tubuh yang terus menerus. Penurunan tersebut menyebabkan penderita mudah terserang infeksi oportunistik dan komplikasinya. Penggunaan ARV dan non-ARV secara bersamaan pada pasien HIV/AIDS memungkinkan terjadinya interaksi obat yang bisa memberikan efek berupa perubahan kadar masing-masing obat atau zat dalam darah. Penelitian ini bertujuan untuk mengetahui persentase terjadinya interaksi pada penggunaan obat ARV dan non-ARV b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…The results showed that more opportunistic infections in patients were tuberculosis infections, with a percentage of 17.5% (21 patients). The results of this study are similar to Kridaningsih (2021) and Yuniarti (2020), which showed that the most comorbidities experienced by tuberculosis HIV/AIDS patients. In addition, Anggriani's research in 2019 also stated that tuberculosis infection (55.6%) was influenced by the level of immunosuppression caused by HIV infection.…”
Section: Resultssupporting
confidence: 86%
“…The results showed that more opportunistic infections in patients were tuberculosis infections, with a percentage of 17.5% (21 patients). The results of this study are similar to Kridaningsih (2021) and Yuniarti (2020), which showed that the most comorbidities experienced by tuberculosis HIV/AIDS patients. In addition, Anggriani's research in 2019 also stated that tuberculosis infection (55.6%) was influenced by the level of immunosuppression caused by HIV infection.…”
Section: Resultssupporting
confidence: 86%